Latin America: Demographic Dynamics and the Migration Processes Transformation - N. Yu. Kudeyarova (Контуры глобальных трансформаций: политика, экономика, право, 2020)
Latin America is one of the high level migration activity regions. The mass migration flows are the part of the Western Hemisphere South nations history for more than a century and a half. Both the structure and direction of that flows have been significantly transformed during that period. While being the transatlantic flows recipients at the end of the XIX – beginning of the XX centuries, the Latin American States turned into donors of human resources in the second half of the XX century due to the profound demographic transformation. The aim of this paper is to analyse the demographic transformations impact on the emigration mobility models development in Latin America and the Caribbean countries. Demographic changes were manifested in different ways in countries with a large share of European migrants and those that were not affected by mass migrations flows at the turn of the XIX – XX centuries. The Central America countries and Mexico have experienced the most profound population explosion that subsequently affected the intensity of the migration movement to the United States. The paper examines the main migration directions of Latin America and the Caribbean residents, identifies two basic mobility source areas that demonstrate different strategies via different destination countries choice. While the United States has become the leading destination country for Latin American migrants, accounting for 93% of migrants from Central America and Mexico, the South American migration is mostly intraregional. The largest regional integration associations migration policies implementation reflects this difference. Spain has become a significant extra-regional migration destination for South America. At the end of the second decade of the XXI century, global economic transformations affect the migration dynamics of Latin American subregions, producing powerful migration crises and local tensions.